The Draw-A-Man Test and raven progressive matrices performance of Guatemalan Maya and Ladino children - Johnson, Dale L.; Johnson, Carmen A.; Price-William, Douglass (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The Draw-A-Man Test and Raven’s Progressive Matrices were administered to a group of highland Guatemalan public school children. The DAMT, administered to 256 children, showed an overall mean IQ of 85. Boys scored significantly higher than girls. There were no important differences between the scores of Indians and Ladinos. The Raven Progressive Matrices test, given to 34 children, also yielded low intelligence scores. Significant correlations between teacher ratings of intelligence and the above tests suggest that these measures have a certain validity in the Guatemalan setting. In spite of the non-verbal nature of the test problems, it seemed likely that formal and informal cultural differences in educational goals functioned to depress the test scores. In addition, low health levels have been associated with the low test performance in other areas and were present in the subject population in the present instance. We suggest that important untapped human resources remain undeveloped in the highlands of Guatemala, and that sensitive and planned social improvement could readily change the present picture.